Speaking like a scientist: A multiple case study on sketch and speak intervention to improve expository discourse. (March 2021) - Peterson, Amy K; Ukrainetz, Teresa A; Risueño, RJ
Purpose: This descriptive multiple case study examined the effects of a contextualized expository strategy intervention on supported and independent note-taking, verbal rehearsal, and reporting skills for three elementary students with language disorders. Method: Two 9-year-old fourth grade students and one 11-year-old sixth grade student with language disorders participated. The intervention was delivered as sixteen individual 20-minute sessions across nine weeks by the school speech-language pathologist. Students learned to take written and pictographic notes from expository texts and use verbal formulation and rehearsal of individual sentences and whole reports in varied learning contexts. To explore both emergent and independent accomplishments, performance was examined in final intervention session presentations and pre/post intervention testing. Results: Following the intervention, all three students effectively used notes and verbal rehearsal to prepare and present fluent, organized, accurate, confident oral reports to an audience. From pre- to post-test, the students showed a range of improvements in the quality of notes, use of verbal rehearsal, holistic quality of oral and written reporting, and strategy awareness. Conclusions: Sketch and Speak shows potential as an expository intervention for students who struggle with academic language learning. The results support further examination of this intervention for supported strategy use by younger students and independent use by older students.